2017
DOI: 10.1002/clen.201500730
|View full text |Cite
|
Sign up to set email alerts
|

Abiological Granular Sludge Formation Benefit for Heavy Metal Wastewater Treatment Using Sulfide Precipitation

Abstract: Solid-liquid separation is a fundamental and ubiquitous process in water purification. Previously, an abiological granular sludge (ABGS) formation strategy was developed to improve the solid-liquid separation in heavy metal wastewater treatment. Although this strategy can be effectively applied in hydroxide precipitation, it remains challenging to apply it to other precipitation processes and real wastewater. Here, conditions for ABGS formation in the sulfide precipitation were first optimized. The effect of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…Furthermore, Cr (VI) gets to humans through drinking water or food such as fish or plants, where it has many hazardous effects on human health. Therefore, many conventional methods were used for chromium removal: ion exchange, electrodialysis, ultrafiltration, chemical precipitation and reverse osmosis (Nataraj et al 2007;Rajput et al 2016;An et al 2017;Yan et al 2017;Zamri et al 2017). However, these technologies are very expensive, generate toxic non-ecofriendly waste material and are not effective at a low chromium concentration (Singh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cr (VI) gets to humans through drinking water or food such as fish or plants, where it has many hazardous effects on human health. Therefore, many conventional methods were used for chromium removal: ion exchange, electrodialysis, ultrafiltration, chemical precipitation and reverse osmosis (Nataraj et al 2007;Rajput et al 2016;An et al 2017;Yan et al 2017;Zamri et al 2017). However, these technologies are very expensive, generate toxic non-ecofriendly waste material and are not effective at a low chromium concentration (Singh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the second case, the use of an abiological granular sludge (ABGS) was used to improve the aggregation and settling of sulfide precipitates. Results showed that the use of an ABGS allowed for a settling velocity of 3.4 m/s for Zn/Pb precipitates from a real wastewater [98]. Finally, the third case showed that the particle size of CdS and a mix of CuS/CdS increased from 1-5 µm to 1000 µm after 30 min of applying UV light irradiation.…”
Section: Latest Breakthroughs In Solid-liquid Separationmentioning
confidence: 90%
“…Studies to optimize the solid-liquid separation in metal sulfide precipitation processes are still emerging, although there are a few interesting examples which could address new research trends. The use of a magnetic field to modify the zeta potential of particles [97], the use of an abiological granular sludge [98], and the use of UV light irradiation to improve the aggregation [99] have been experiments conducted to enhance the settling rate of particles. In the first case, the application of a magnetic field of 2T for 40 min increased the zeta potential from −40 mV to 16.5 mV.…”
Section: Latest Breakthroughs In Solid-liquid Separationmentioning
confidence: 99%
“…CrI was calculated according to the following equation [ 51 ]: where I 002 is the peak intensity corresponding to the (002) lattice plane of cellulose I, and I am is the peak intensity observed at 2θ = ~ 18.5°. Fourier Transform infrared (FTIR) spectra of the CS samples were recorded on a Nicolet IS10 spectrometer in the range 4000–400 cm −1 [ 52 ]. The CS samples were mixed with KBr, ground to a fine powder, and pressed into pellets for the infrared transmission studies.…”
Section: Methodsmentioning
confidence: 99%